Relative age effects in fitness testing in a general school sample: how relative are they? - Veldhuizen, S.; Cairney, J.; Hay, J.; Faught, B. (Journal of Sports Sciences, 2015)
When children or adolescents are grouped by age or year of birth, older individuals tend to outperform younger ones. These phenomena are known as relative age effects (RAEs). RAEs may result directly from differences in maturation, but may also be associated with psychological, pedagogic or other factors. In this article, we attempt to quantify RAEs in a simple fitness task and to identify the mechanisms operating.